HUBUNGAN KESEPIAN DENGAN KECANDUAN INTERNET PADA MAHASISWA - Sunarko Sunarko; Intan Maranata; Aisyah Nur Izzati; Angga Sugiharto; Suharsono (Midwifery and Nursing Research, 2026)
Relationship Between Loneliness And Internet Addiction Among Students Intan Maranata1, Sunarko2, Aisyah Nur Izzati3, Angga Sugiarto4, Suharsono5 Email : sunarko@poltekkes-smg.ac.id ABSTRACT Background: loneliness is a common mental health issue among university students and can trigger various psychological disorders, including internet addiction. Students who live far from their families often experience loneliness and seek escape through excessive internet use. However, the mechanism underlying the relationship between loneliness and internet addiction still needs to be further understood, especially in the context of nursing students. This study aims to examine the relationship between the level of loneliness and the level of internet addiction among students in the Nursing Study Program at Magelang, Health Polytechnic Semarang. Methods: this research used a descriptive correlational design with a cross- sectional approach. A total of 180 students from second semester, fourth semester, and sixth semester were selected using cluster sampling techniques. The instruments used were the University of California Los Angeles (UCLA) Loneliness Scale Version 3 to measure loneliness, and the Internet Addiction Test (IAT) to measure the level of internet addiction. Data were analyzed using Spearman’s rho test. Results: the results showed that 92.2% of students experienced a moderate level of loneliness and 54.4% showed a mild level of internet addiction. Spearman’s rho correlation analysis indicated a significant positive relationship between loneliness and internet addiction (r = 0.176; p < 0.018). Conclusion: there is a significant positive relationship between loneliness and internet addiction among students. The higher the level of perceived loneliness, the higher the tendency to experience internet addiction. Keyword : internet addiction; loneliness 1234 Department of Nursing Study Program Magelang, Polytechnic of Health Semarang Jl. Perintis Kemerdekaan No. 143 Kramat Utara, Magelang Utara, Kota Magelang, Jawa Tengah, Indonesia.